Response times for reflexive saccades correlate with cognition in parkinson's disease, not disease severity or duration - Yu, Yaqin; Yan, Weihong; Xu, Xin; Zhang, Kaili; Si, Lihong; Liu, Xiaolei; Wang, Jinyu; Song, Junling; Sun, Huanxin; Li, Xinyi (Frontiers in Neurology, 2022)
Objective: Dementia is a common and serious non-motor symptom in Parkinson’s disease (PD). We aimed to investigate the reflexive saccade in PD patients and explore its potential role as a biomarker for cognitive decline. Methods: Using an infrared video-based eye tracker, we investigated reflexive saccades in 94 PD patients and 115 healthy controls (HCs). Saccadic parameters were compared between PD patients and HCs, and also among PD subgroups. The correlation of saccadic parameters with disease duration, severity and cognition were further investigated. Results: Compared with healthy controls, PD patients had prolonged and hypometric reflexive saccades even in early disease stage. In PD patients, reflexive saccadic latency was inversely correlated to MMSE score and AUC of the ROC analysis was 0.63; reflexive saccadic gain was in a negative relation with disease duration; reflexive saccadic velocity differed significantly between tremor dominant (TD) patients and postural instability/gait difficulty (PIGD) patients, with TD patients showing a significant lower velocity than PIGD patients. Conclusion: Reflexive saccadic performance was abnormal in PD and worsened with cognitive decline. The negative correlation between latency and MMSE scores may make the reflexive saccade a potential predictor for cognitive decline in Parkinson’s disease.